A high precision analog multiplexer for multi-channel neural recording micro-systems. (January 2018) - Naghavi, Saeed; Sharifi, Niloofar; Abrishamifar, Adib
Abstract: This paper introduces a high precision analog multiplexer to be used in multi-channel neural recording micro-systems. In any time-division multiplexing (TDM) system, the accuracy of the analog switches within the multiplexer is a critical parameter to determine overall performance of the system. To satisfy the accuracy requirements of the switch, a novel technique to minimize the charge injection and clock feed-through errors by using a very simple structure is proposed. Moreover, an innovative approach to increase the off-resistance of the switch and consequently minimizing its leakage current is presented. In order to evaluate the performance of the proposed switch, simulations are done in a 0.18 μm standard CMOS technology. Simulation results show that switch induced errors are significantly eliminated by using the proposed cancellation technique. The output error charge due to charge injection and clock feed-through over a wide range of the input signal variation is very low (less than 1.53 fC). Also Simulation results show that the proposed switch achieves signal to noise plus distortion ratio (SNDR) of 100.6 dB, effective number of bits (ENOB) of 16.42, total harmonic distortion (THD) of −100.88 dB and spurious-free dynamic range (SFDR) of 101.47 dB for a 1 kHz sinusoidal input of 800 mv peak-to-peak amplitude at 20 kHz sampling rate with a 1.8 V supply voltage. In addition to the switched induced errors, special care has to be taken with regard to the crosstalk effects while designing of the analog multiplexers. In this work, by using an appropriate analog switch with considering crosstalk requirements, using suitable buffers prior to the multiplexer input channels and designing a proper layout, the total crosstalk between adjacent channels is negligible. The post layout simulation of crosstalk shows that the total crosstalk at a sampling rate of 20 kHz per channel is less than −80 dB.